Clostridium difficile Infection: Epidemiology, Pathogenesis, Risk Factors, and Therapeutic Options - Mehdi Goudarzi; Sima Sadat Seyedjavadi; Hossein Goudarzi; Elnaz Mehdizadeh Aghdam; Saeed Nazeri (Scientifica)
The incidence and mortality rate of Clostridium difficile infection have increased remarkably in both hospital and community settings during the last two decades. The growth of infection may be caused by multiple factors including inappropriate antibiotic usage, poor standards of environmental cleanliness, changes in infection control practices, large outbreaks of C. difficile infection in hospitals, alteration of circulating strains of C. difficile, and spread of hypervirulent strains. Detection of high-risk populations could be helpful for prompt diagnosis and consequent treatment of patients suffering from C. difficile infection. Metronidazole and oral vancomycin are recommended antibiotics for the treatment of initial infection. Current treatments for C. difficile infection consist of supportive care, discontinuing the unnecessary antibiotic, and specific antimicrobial therapy. Moreover, novel approaches include fidaxomicin therapy, monoclonal antibodies, and fecal microbiota transplantation mediated therapy. Fecal microbiota transplantation has shown relevant efficacy to overcome C. difficile infection and reduce its recurrence.